Studi Deskriptif Hasil Karya Mozaik Berbahan Dasar Biji Kopi pada Pembelajaran SBdP Siswa Kelas III SDN 80 Rejang Lebong - Ridho Permadi; Hasnawati; Neza Agusdianita (UNIB Press, 2023)
This study aims to describe the results of mosaic works made from coffee beans on SBdP content of class III students at SDN 80 Rejang Lebong. This type of research is a qualitative descriptive research, with observation techniques, interviews and documentation. The subjects of this study were 4 mosaic works by class III students at SDN 80 Rejang Lebong. The research instrument used is the human instrument. Data collection techniques in the form of observation, interviews, and documentation. The data analysis technique used is a qualitative descriptive technique using the Miles & Huberman interactive model. The results of the research on 4 mosaic works contained 6 elements, namely dot elements applied using coffee beans in the drawing pattern, line elements were applied in making picture patterns, plane elements were non-geometric or irregular, white elements were applied to the base/background and the original color of the seeds coffee, two-dimensional shape elements have no volume, real and grainy texture elements. The results also show that there are 4 principles, namely the principle of rhythm is found in the arrangement of coffee beans, the principle of balance is found in good repetition, the principle of unity is seen from the orderly arrangement of coffee beans, the principle of center of attention shows the characteristics of the work of each group. In making coffee bean mosaics, the elements and principles of fine art have been applied.